A incidência (ou não) da contribuição previdenciária patronal sobre os planos de opções de ação (Stock Options Plan) outorgados a empregados - Nakayama, Ellen (2018)
This paperwork is a theorectical study regarding the possibility of Brazilian social security contribution levy on stock options’ plans offered by the companies to their employees, considering the matrix-rule of tax incidence, the social security system’ finance and labor law concepts, which were crucial to define the legal nature of it and to analyse doctrine and former court decision rendered in scope of Labor Law and Tax Law